Experimental comparison of heat transfer characteristics of Enhanced Truck Radiators - Hatice Mercan; Furkan Sonmez; Ahmet Selim Dalkilic; Somchai Wongwises (Case Studies in Thermal Engineering, 2022)
In the current experimental investigation, the radiators’ heat transfer performances are evaluated experimentally and validation is done using the analytical ε-NTU method. In this experimental study composition of the cooling fluid is 50:50 water/EG. The pressure and temperature values are fixed for air and water/ethylene glycol sides. The velocity of air is between 1.5−12 m/s and water/ethylene glycol flow rate is between2.5−7 kg/s. All measurements are performed after steady state is reached. For altering operation conditions, the overall heat transfer coefficient, exit water/ethylene glycol temperature, pressure drop and friction coefficients are evaluated experimentally. Both rate of heat transfer and the pressure drop are maximum for the double U grooved case. For the tested radiator categories, the overall heat transfer coefficient rose with increasing coolant and air velocity and the exit temperature raised with increased coolant flow rate and decreased with increasing velocity of air.